Testing the interrelationship between mental well-being and mental distress in young people. Issue 3 (3rd May 2020) - Hides, Leanne; Quinn, Catherine; Stoyanov, Stoyan; Cockshaw, Wendell; Kavanagh, David J.; Shochet, Ian; Deane, Frank; Kelly, Peter; Keyes, Corey L. M.
ABSTRACT: The relationship between mental well-being and distress in young people is unclear but important for both theoretical and practical reasons. This study tests these relationships using both dimensional and categorical measures of mental well-being and distress. Two thousand and eighty-two Australians' (16–25 years) completed an online survey. A subsample (n = 389) completed diagnostic telephone interviews to identify 12-month DSM-IV mood, anxiety and substance use disorders. Five competing models of the relationship between mental well-being and distress were compared. Only the bifactor model fit the data, indicating both mental well-being and distress are important subcomponents of a young person's overall level of mental health. Over 90% of young people had flourishing or moderate well-being and only 6% were languishing. Those with past year mental disorders were only 15% less likely to be flourishing and 4% more likely to be languishing. These findings highlight the well-being potential of young people living with and without mental disorders.